HUBUNGAN AKTIVITAS FISIK DAN PERILAKU MAKAN MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2018 SAAT PENDEMI - CHUSNUL ATIKA; AMELIA EKA DAMAYANTI (LP2MTBM MAKARIOZ, 2023)
New type of Corona virus or SARS-CoV-2 which is spreading rapidly throughout the world, so WHO declared the Covid-19 outbreak a pandemic. Likewise, the Indonesian government has implemented large-scale social restrictions to suppress the spread of Covid-19. One of them is in the field of education, where learning is done online. Online academic activities can cause problems for physical health, due to physical inactivity and sedentary activities continuously. As a result of isolation activities and restrictions on these activities can also cause stress, where one response to stress is to increase food intake, especially delicious and energy-dense foods. To determine the relationship between physical activity and eating behavior in students at the Faculty of Medicine, University of Muhammadiyah North Sumatra, Class of 2018 during a pandemic. This study was conducted using a descriptive analytic method with a cross sectional design in December 2021 at the Faculty of Medicine, University of Muhammadiyah North Sumatra. Based on the results of the analysis, the demographic characteristics of the age group were mostly found at the age of 21 years –25 years with a total of 84 people (83.2%), the frequency of high physical activity being the highest number, namely 38 people (37.6%) and the frequency of unhealthy eating behavior. had the highest number of 56 people (55.4%) with p value = 0.001. There is a significant relationship between physical activity and eating behavior of students of the Faculty of Medicine, University of Muhammadiyah North Sumatra class 2018 during the pandemic.